Successful management of heterotopic cornual pregnancy with laparoscopic cornual resection. (August 2016) - Kim, Myung Joo; Jung, Yong Wook; Cha, Jae-Ho; Seok, Hyun Ha; Han, Ji Eun; Seong, Seok Ju; Kim, You Shin
Abstract: Objective: To examine the feasibility of laparoscopic cornual resection for the treatment of heterotopic cornual pregnancy. Study design: Women who underwent laparoscopic cornual resection for heterotopic cornual pregnancy at our hospital between January 2003 and March 2015 were retrospectively analyzed. We evaluated significant parameters such as operative complications and postoperative pregnancy outcomes of concomitant pregnancy. Results: Thirteen patients with heterotopic cornual pregnancy were included in the study. All were pregnant through assisted reproductive technology, and the diagnosis was made at a median of 6 + 6 weeks (range 5 + 4–10 + 0). They were successfully treated with laparoscopic cornual resection and admitted for a median of 4 days (range, 2–7) postoperatively. The median operative time was 65 min (range, 35–145 min) and estimated blood loss was 200 mL (range, 10–3000 mL). There was a spontaneous abortion at 7 + 6 gestational weeks in a patient who received bilateral cornual resection. Seven patients delivered babies at term and 3 at preterm. All 10 women delivered without any maternal or neonatal complications. Two were lost to follow-up. Conclusions: Laparoscopic cornual resection is a feasible primary approach for the management of heterotopic cornual pregnancy.